Blockchain and Machine Learning Empowered Internet of Things Applications: Current Issues, Challenges and Future Research Opportunities - Gomathi, L.; Mishra, Anand Kumar; Tyagi, Amit Kumar (2023 4th International Conference on Smart Electronics and Communication (ICOSEC), 2023)
Two advanced technologies that have the potential to revolutionise the Internet of Things (IoT) ecosystem are blockchain and machine learning, as they address a wide range of issues, including data security, interoperability, and scalability. However, there are a number of barriers to integrating these technologies, such as issues with trust, reliability, and governance. This research study summarises the current state of the BML-IoT applications and identifies the challenges and issues encountered in developing these applications. It also discusses possible directions for future research on BML-IoT applications for smart cities, energy management, smart homes, smart agriculture, smart education, and smart healthcare. Overall, this study contributes to a better understanding of the endless possibilities of BML-IoT applications and the research challenges that need to be addressed to fully realise their potential.